2010
DOI: 10.1111/j.1523-1739.2009.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Artificial Habitats for Amphibian Reproduction in Altered Landscapes

Abstract: Installation and maintenance of stormwater ponds to detain and treat runoff from impervious surfaces is a common method of stormwater control in developed areas. That these ponds capture pollutants, however, is of concern for wildlife species that use the ponds, particularly pond-breeding amphibians. To assess the relative contribution of stormwater ponds to the persistence of amphibian populations in suburban landscapes, we compared amphibian use of stormwater ponds and other available wetlands in suburban an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 32 publications
1
88
1
Order By: Relevance
“…However, this study provided evidence of the benefits of artificial MTPs for amphibian conservation already within a short-term period. Other short-term studies in recovered wetlands have shown that anuran densities can be similar to or even higher than the densities in natural wetlands (e.g., Balcombe et al, 2005;Brand and Snodgrass, 2010). Hence, in such situations artificial wetlands may help recover declining populations of threatened species (Rannap et al, 2009).…”
Section: Conservation Interest Of Man-made Mtpsmentioning
confidence: 96%
“…However, this study provided evidence of the benefits of artificial MTPs for amphibian conservation already within a short-term period. Other short-term studies in recovered wetlands have shown that anuran densities can be similar to or even higher than the densities in natural wetlands (e.g., Balcombe et al, 2005;Brand and Snodgrass, 2010). Hence, in such situations artificial wetlands may help recover declining populations of threatened species (Rannap et al, 2009).…”
Section: Conservation Interest Of Man-made Mtpsmentioning
confidence: 96%
“…The total biodiversity recorded within urban ponds was comparable to ponds in the wider landscape around the town of Loughborough (semi-natural meadow ponds = 175 taxa; agricultural ponds = 127 taxa). High regional invertebrate diversity has also been recorded within aquatic urban systems in the Netherlands (Vermonden et al, 2009) and for other organisms such as waterbirds (Santoul et al, 2009) and amphibians (Brand and Snodgrass, 2009).…”
Section: Macroinvertebrate Diversitymentioning
confidence: 90%
“…Due to large scale landscape alterations and the loss of natural wetlands, stormwater ponds and other anthropogenic or constructed aquatic environments may be the only available habitat for amphibians in suburban areas (Brand & Snodgrass, 2010). The quality and suitability of aquatic habitats is determined by hydroperiods, biotic community structure, littoral shelves, and water chemistry (Semlitsch, 2002).…”
Section: Lenthic Habitat Compositionmentioning
confidence: 99%
“…In order for golf course ponds to provide breeding habitat for species of conservation concern, they must be free of predatory fish and American Bullfrogs (Boone, Semlitsch, & Mosby, 2008;Kats & Ferrer, 2003;Shulse, Semlitsch, Trauth, & Williams, 2010) which requires seasonal drying regimes (Maret, Snyder, & Collins, 2006). With proper design, anthropogenic aquatic environments in suburban areas can serve as breeding habitats for amphibian populations while still serving their intended functions (Brand & Snodgrass, 2010).…”
Section: Introductionmentioning
confidence: 99%